2018
DOI: 10.1186/s12889-018-5870-2
|View full text |Cite
|
Sign up to set email alerts
|

Built and natural environment planning principles for promoting health: an umbrella review

Abstract: BackgroundThe built and natural environment and health are inextricably linked. However, there is considerable debate surrounding the strength and quality of the evidence base underpinning principles of good practice for built and natural environment design in promoting health. This umbrella review aimed to assess relationships between the built and natural environment and health, concentrating on five topic areas: neighbourhood design, housing, food environment, natural and sustainable environment, and transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 12 publications
(25 reference statements)
3
88
1
2
Order By: Relevance
“…Other perspectives have had a greater acceptance amongst urban planners and designers, especially participatory approaches (Blancafort and Reus, 2015;Rowe, 2004) and feminist planning (Ortiz Escalante and Gutiérrez Valdivia, 2015). The inclusion of health criteria in public space design is still incipient, even if several authors have worked on tools that may assist planners and designers to conceptualize, design and build with a health perspective (Bird et al, 2018;Public Health Scotland, 2019). It remains to be seen how these ideas are mainstreamed and what physical form they will take.…”
Section: Will the Pandemic Accelerate The Mainstreaming Of Health Crimentioning
confidence: 99%
“…Other perspectives have had a greater acceptance amongst urban planners and designers, especially participatory approaches (Blancafort and Reus, 2015;Rowe, 2004) and feminist planning (Ortiz Escalante and Gutiérrez Valdivia, 2015). The inclusion of health criteria in public space design is still incipient, even if several authors have worked on tools that may assist planners and designers to conceptualize, design and build with a health perspective (Bird et al, 2018;Public Health Scotland, 2019). It remains to be seen how these ideas are mainstreamed and what physical form they will take.…”
Section: Will the Pandemic Accelerate The Mainstreaming Of Health Crimentioning
confidence: 99%
“…The built environment is human-made or modified surroundings, such as buildings, land use (e.g., layout of communities, transportation systems, infrastructures), or green space (12). Research has indicated that built environments and health issues are inextricably linked, because exposure factors affects body condition of human beings (103). Patterns of land development, transportation infrastructure, and building location and design-the built environment could affect the natural environment by replacing natural areas and changing functions and services of ecosystem, which are closely related to the exposure of human beings in the environment.…”
Section: Built Environmental Factorsmentioning
confidence: 99%
“…Controlled experimentation is rarely feasible in the economic evaluation of NE interventions because of the cost and complexity of such studies. Evaluations of NE interventions are thus overwhelmingly based on observational data and any causal inference is limited by potential bias arising from uncontrolled baseline differences between intervention and control groups [ 9 ]. When considering utilising a before and after approach, it is important to note that NE interventions are often added into a system over time, and so it is difficult to determine when the intervention period begins and the control period stops.…”
Section: Methodological Challenges In Conducting Economic Evaluatimentioning
confidence: 99%
“…Environmental interventions are multifaceted and are expected to impact health via several pathways such as by reducing exposure to environmental risk factors, promoting physical activity, and improving mental health [ 9 ]. The links between risk factors and health conditions may be inter-dependent and not independently additive.…”
Section: Methodological Challenges In Conducting Economic Evaluatimentioning
confidence: 99%